1990
DOI: 10.1063/1.103558
|View full text |Cite
|
Sign up to set email alerts
|

Intense photoluminescence between 1.3 and 1.8 μm from strained Si1−xGex alloys

Abstract: Intense photoluminescence (PL) from strained, epitaxial Si1−xGex alloys grown by molecular beam epitaxy is reported with measured internal quantum efficiencies up to 31% from random alloy layers, single buried strained layers, and multiple quantum wells. Samples deposited at ∼400 °C exhibited low PL intensity, whereas annealing at ∼600 °C enhanced the intensity by as much as two orders of magnitude. This anneal treatment was found to be optimal for removal of grown-in defect complexes without creating a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…27 Considering nonradiative carrier recombination associated with structural defects ͑e.g., dislocations͒, we note that ͑i͒ previous TEM studies do not reveal any significant amount of dislocations and ͑ii͒ our PL measurements do not show any specific, dislocation related PL lines ͑i.e., D1, D2, etc.͒ that are normally observed in highly dislocated Si/SiGe samples. 28,29 In conclusion, we have shown that higher than 50% Ge concentration in 3D Si/Si 1Ϫx Ge x nanostructures grown under conditions close to S-K growth mode induces Ge segregation in the form of Ge-core/SiGe shell nanoclusters. These clusters exhibit an efficient, extending almost to room temperature, PL.…”
mentioning
confidence: 66%
“…27 Considering nonradiative carrier recombination associated with structural defects ͑e.g., dislocations͒, we note that ͑i͒ previous TEM studies do not reveal any significant amount of dislocations and ͑ii͒ our PL measurements do not show any specific, dislocation related PL lines ͑i.e., D1, D2, etc.͒ that are normally observed in highly dislocated Si/SiGe samples. 28,29 In conclusion, we have shown that higher than 50% Ge concentration in 3D Si/Si 1Ϫx Ge x nanostructures grown under conditions close to S-K growth mode induces Ge segregation in the form of Ge-core/SiGe shell nanoclusters. These clusters exhibit an efficient, extending almost to room temperature, PL.…”
mentioning
confidence: 66%
“…For example, room-temperature visible photoluminescence (PL) has been observed from porous Si [1] and strong infrared PL from various island or quantum dot systems [2][3][4][5][6][7][8][9]. A particular focus has been the study of self-organized structures containing nanometer sized Si and Ge crystals [10] which being compatible with present Si technology have important capabilities for device engineering.…”
Section: Introductionmentioning
confidence: 98%
“…For example, room-temperature visible photoluminescence (PL) has been observed from porous Si (1) and strong infrared PL from various island or quantum dot systems (2)(3)(4)(5)(6)(7)(8)(9). A particular focus has been the study of self-organized structures containing nanometer sized Si and Ge crystals (10), which being compatible with present Si technology have important capabilities for device engineering.…”
Section: Introductionmentioning
confidence: 98%